Propagation characteristics of low-frequency acoustic wave in full waveguide of shallow water based on time-domain finite element method. Issue 1 (April 2021) - Wang, Qile; Zhu, Hanhao; Tang, Yunfeng; Xiao, Rui; Xue, Yangyang
Abstract: In order to clarify the propagation mechanism and characteristics of low-frequency sound signals in shallow sea with elastic bottom, using the Time-domain Finite Element Method (TDFEM), a time-domain numerical calculation model of the low-frequency sound field in shallow sea full-waveguide under the action of a point sound source is established. With this model, The influence of seabed acoustic parameters' and seabed topography' changes on the sound propagation characteristics in full-waveguide is simulated and analyzed. The results show that when there is a shear wave effect on the seabed, low-frequency sound waves will excite the Scholte wave propagating on the bottom boundary of the seabed. The greater the seabed acoustic impedance, the faster the excited Scholte wave velocity and the large the amplitude. At the same time, there will be acoustic energy leakage phenomenon in the inclined seabed.